THE ANALYSIS OF TEACHING THINGS THROUGH ORAL REPETITION - Octa Pratama Putra (LPPM Universitas Bina Sarana Informatika, 2014)
Every single teacher has different style of using method and the techniques of teaching English as the topic. Talking about techniques, one of them is the using of oral repetition. The use of this technique had been applied to the level of beginner level of the elementary students at a private English course at Cibinong. At that time, that teaching opportunity was entitled the things in the classroom where the teacher takes from the closest things from the life of the students. Absolutely, as the result is amazing and works well. From the side of the passion of the learners, they were zealous and felt enthusiastic. The pupils really had their time during learning activity occurred. They had to speak together, especially they had to open their mouth and speak loud at the same time with the others. From that activity, it can be concluded that it also has the equal effect of the assessment. Certainly, the score overall was great and awesome.